Socio-Cultural Adaptation Of The Community In Facing New Habits During The Covid-19 Pandemic In The Liliba Village, Kupang City - Imanta Immanuel PERANGINANGIN; Syamsuriady SYAMSURIADY; Hotlif A. NOPE; Aelsthri NDANDARA (Journal of Tourism Economics and Policy, 2023)
This study examines how urban communities in Iliba Village, Kupang City adjust to the New Habit Adaptation program. To find a suitable model or solution for social policy studies, a community's attitude toward adapting to new habits and socio-cultural adaptability is described. The object was Kupang City's Liliba Village residents. The object was chosen because Liliba Village had a high number of cases since the start of the COVID-19 epidemic, and the research approach was a qualitative paradigm based on case studies. This study highlights direct informant empirical experiences. In-depth interviews, FGDs, and literature reviews collected data, which was then examined qualitatively. The study found that the Covid-19 Pandemic forced the community to be more adaptive to various forms of social change that occurred, especially to changes in the social conditions of the Liliba Village community who avoided crowds, there was a change in Stigma Against Other Individuals, making adjustments to interactions according to pandemic conditions and changes to communication models. While changes in the cultural conditions of the people of Liliba Village include not kissing the nose, receiving guests, and religious and worship activities in their homes, the response to the implementation of new habits is to be more responsive to the threat of coronavirus transmission and more anticipatory in public interactions.